(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
The article discusses the work developed by the Máskara Group – Transdisciplinary Research Center in Theatre, Dance and Performance – in the training of artists in the scene who are seriously seeking to understand the depth of theatrical practice as an experiment and research. In this sense, I present my experience in the group as an artist, illuminator and researcher. Therefore, I demonstrate the creative process of light in the play Senhora dos Afogados (1947) by the Brazilian playwright Nelson Rodrigues (1912-1980), staged by Dr. Robson Corrêa de Camargo in 2012 in the city of Goiânia, Goiás. The problematization of this research was structured in the pictorial study of the Dutch plastic artist Rembrandt Van Rijn (1606-1669) in his works on light and shadow. Therefore, the creative process of light by Senhora dos Afogados, supported by the perspective of light and shadow in Rembrandt’s work, points to the relevance of theoretical and practical research for the production of the Grupo Máskara scene.